2023
DOI: 10.1177/00469580231165858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Otago Exercise Program on Physical and Psychosocial Functions Among Community-Dwelling and Institutionalized Older Adults: A Scoping Review

Abstract: To review the effects of Otago exercise program (performed individually or in group) on several physical and psychosocial outcomes for community-dwelling and institutionalized older adults. Fourteen articles met the inclusion criteria. Three electronic databases and reference lists of identified studies were searched. Eligibility criteria included clinical trials of the Otago exercise program conducted among older adults. Two studies were conducted in institutions, 2 in groups. None of the studies reviewed rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In recent years, it has also been performed as group training which gives a more interesting and socializing character with similar results [19]. Specifically, very recent systematic reviews and meta-analyses have confirmed that the group format for the OEP is more effective for improving static balance, dynamic balance, and perceived balance-measured by reporting fear of falling and older adult's confidence in maintaining balance-as well as physical functioning, than the individual format [20][21][22].…”
Section: Introductionmentioning
confidence: 90%
“…In recent years, it has also been performed as group training which gives a more interesting and socializing character with similar results [19]. Specifically, very recent systematic reviews and meta-analyses have confirmed that the group format for the OEP is more effective for improving static balance, dynamic balance, and perceived balance-measured by reporting fear of falling and older adult's confidence in maintaining balance-as well as physical functioning, than the individual format [20][21][22].…”
Section: Introductionmentioning
confidence: 90%
“…The risk of falls in the intervention group decreased from 14.26 to 12.05 s and increased from 12.94 to 13.26 s in the control group. In their scoping review, Mgbeojedo et al [104] reported that when the OEP was administered in either group setting or on an individualized basis, it effectively reduced falls. Additionally, balance, strength, mobility, and health-related quality of life within the community and institutionalized older adults were improved.…”
Section: Therapeutic Exercises In Fall Managementmentioning
confidence: 99%